2015
DOI: 10.14256/jce.1163.2014
|View full text |Cite
|
Sign up to set email alerts
|

Izobrazba o primjeni BIM-a kao podrške integriranom projektiranju

Abstract: Izobrazba o primjeni BIM-a kao podrške integriranom projektiranjuPovećanje opsega projekta, ambicioznih projektnih ciljeva i broja sudionika u procesu planiranja zahtijeva učinkovito integrirano planiranje i prikladnu računalnu podršku, poput BIM alata (eng. Building Information Modelling -BIM). Vještine rada u BIM-u, a koje se traže u praksi, nisu zastupljene u nastavnim planovima i programima tehničkih sveučilišta. U ovom se radu prikazuje provedba interdisciplinarne BIM projektne izobrazbe na Tehničkom sveu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The authors of the aforementioned paper underlined the necessity of multidisciplinary structured teams for structuring national frameworks and regulations, which would ease the transition of BIM from educational to practical uses, a conclusion shared by the authors of [20] as well. These theses were partially confirmed in the research published in [21], which revealed Croatian AEC practitioners are familiar with the concepts of BIM but in most cases have not yet implemented it in their projects.…”
Section: Bim In Croatiamentioning
confidence: 96%
“…The authors of the aforementioned paper underlined the necessity of multidisciplinary structured teams for structuring national frameworks and regulations, which would ease the transition of BIM from educational to practical uses, a conclusion shared by the authors of [20] as well. These theses were partially confirmed in the research published in [21], which revealed Croatian AEC practitioners are familiar with the concepts of BIM but in most cases have not yet implemented it in their projects.…”
Section: Bim In Croatiamentioning
confidence: 96%
“…These educationalists' focus in expanding the BIM course was specifically students who are interested in BIM management positions. Aside from these experimental efforts on multidisciplinary BIM courses made by BIM educationalists and researchers in the USA, Kovačić et al (2015) from the Institute for Interdisciplinary Building Process Management of Vienna University of Technology, Austria also reported on an interdisciplinary BIM design course. Through observations gained from their focus group study on multidisciplinary student teams, they concluded several recommendations for future interdisciplinary BIM courses: (a) impose a firm time schedule, (b) enforce verified software combinations, (c) set clear rules and responsibilities, and (d) design same input (course credits) for same course output among multidisciplinary students.…”
Section: Architectural Engineeringmentioning
confidence: 99%
“…Based on the theories illustrated in previous studies [3][4][5][6][7], many grouted splices in which bars were spliced in line were invented [1,[8][9][10][11][12][13][14][15]. However, the construction of the sleeve was rather complicated, and manufacturing was relatively expensive.…”
Section: Introductionmentioning
confidence: 99%